Monthly Trends in Drug Overdose Mortality among Youth Aged 15-34 Years in the United States, 2018-2021: Measuring the Impact of the COVID-19 Pandemic - Hyunjung Lee; Gopal K. Singh (Global Health and Education Projects, Inc., 2022)
Background: Adolescents and young adults in the United States (US) have experienced a significant increase in drug overdose mortality rates in the last two decades. During the Coronavirus disease 2019 (COVID-19) pandemic, they experienced a lack of access to substance use disorder treatment, stay-home orders, school closure, social isolation, increased psychological distress, and financial strain. Few studies have examined the impact of the pandemic on monthly trends in drug-overdose mortality among youth by race/ethnicity. This study estimates differential changes in monthly drug overdose mortality among youth in the US by age, sex, and race/ethnicity. Methods: Monthly deaths from the final 2018-2020 national mortality data and the 2021 provisional mortality data were used, and monthly population estimates were obtained from the Census Bureau. We calculated age-specific monthly drug overdose deaths per one million population and used log-linear regression models to estimate monthly percent increases in mortality rates from January 2018 through October 2021. Results: Drug-overdose deaths among individuals aged 15-34 increased by 36.5% from 2019 (21,152 deaths) to 2020 (28,879 deaths). From February 2020 to May 2020, the drug-overdose mortality rate increased by 62% for males, 53% for females, 79% for Blacks, 62% for American Indians/Alaska Natives (AIANs), 57% for Hispanics, 56% for non-Hispanic Whites, and 47% for Asians. From January 2018 to October 2021, the average monthly drug-overdose mortality rate increased by 2.69% per month for Blacks, 2.54% for AIANs, 2.27% for Hispanics, 1.37% for Asians, and 0.81% for non-Hispanic Whites. Increases in drug-overdose mortality were more rapid among males than females and among youth aged 15-24 than youth aged 25-34. Conclusion and Global Health Implications: During the peak months in 2020 and 2021, the COVID-19 pandemic had a disproportionate impact by race/ethnicity on trends in drug overdose mortality among the youth. Drug overdose mortality rates increased faster among Blacks, Hispanics, AIANs, and Asians compared to non-Hispanic Whites.   Copyright © 2022 Lee and Singh. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0.